Francesco Manganaro, Alessio Altadonna, Adriana Arena. Mario Manganaro “…un disegnatore generoso” Messina: EDAS Editori 2018 (diségno, 2018)
The book here exposed is the exhibition catalogue of MM I RICORDANDO una mostra di disegni di Mario Manganaro, but it is also much more, collecting, next to drawings, texts written by friends, family, students and colleagues of Mario Manganaro to ensure memories, shared practice, thoughts addressed to him.Edited by Francesco Manganaro, Alessio Altadonna and Adriana Arena, the book, entitled Mario Manganaro “… un disegnatore generoso”, published by EDAS, collects ninety-five Drawings by M.M. on the left pages and sixty-one Drawings by M.M. exhibited (drawings are cataloged by title, year, place, size, technique, support), side by side to fifty-five textual contributions signed by the same numbers of authors (read more).